Belief elicitation in experiments: is there a hedging problem? - Mariana Blanco; Dirk Engelmann; Alexander K. Koch; Hans-Theo Normann (Institute for the Study of Labor (IZA), 2008)
Belief elicitation in economics experiments usually relies on paying subjects according to the accuracy of stated beliefs in addition to payments for other decisions. Such incentives, however, allow risk-averse subjects to hedge with their stated beliefs against adverse outcomes of other decisions in the experiment. This raises two questions: (i) can we trust the existing belief elicitation results, (ii) can we avoid potential hedging confounds? Our results instill confidence regarding both issues. We propose an experimental design that eliminates hedging opportunities, and use this to test for the empirical relevance of hedging effects in the lab. We find no evidence for hedging, comparing the standard hedging-prone belief elicitation treatment to a hedging-proof design in a sequential prisoners dilemma game. Our findings are strengthened by the absence of hedging even in an additional non-belief elicitation treatment using a financial investment frame, where hedging arguably would be most natural.
urn:nbn:de:101:1-20080605121
Keywords: C72; 330; Belief elicitation; hedging; methods; experimental economics; Nichtkooperatives Spiel; Test; Erwartungstheorie; Ökonomischer Anreiz; Hedging; Verhaltensökonomik